Perineal Injury During Childbirth Increases Risk of Postpartum Depressive Symptoms and Inflammatory Markers - Dunn, Alexis B. (J Midwifery Womens Health, 2015)
INTRODUCTION: Perineal lacerations during childbirth affect more than 65% of women in the United States. Little attention has been given to the long-term biologic consequences associated with perineal lacerations or possible associations with postpartum mental health. In this article we describe the results of a study that explored inflammatory pathways in women who reported perineal lacerations during childbirth and the relationship with stress and depressive symptoms during the first six months postpartum. METHODS: A repeated measures design was used to explore the relationship between varying degrees of perineal lacerations, inflammatory cytokines, postpartum stress, and depressive symptoms in 153 women over six months. Depressive symptoms were measured using the Edinburg Postnatal Depression Scale (EPDS) and maternal stress via the Perceived Stress Scale (PSS). Plasma was analyzed for pro (TNF-α, IL-6, IL-1β, IFN-γ) and anti-inflammatory (IL-10) cytokines. Levels of cytokines were compared between women with or without varying degrees of injury. RESULTS: A relationship was identified between symptoms of depression and a 2(nd) degree or more severe perineal laceration starting at 1 month postpartum (P=0.04) and continuing through 3 months (P=0.03). Similarly, stress symptoms were higher at 3 months postpartum (P=0.02). Markers of inflammation were significantly higher among this group with IL-6 increased at 2 weeks postpartum (P=0.02), and remaining elevated through 2 months postpartum (P=0.003); there were also significant differences in pro to anti-inflammatory cytokine ratios out to 6 months postpartum. Regression analysis indicated that 2(nd) degree or more severe lacerations accounted for 5.9% of the variance in EPDS score at one month postpartum (P=0.024, F=2.865, t=2.127), increasing substantially when the 1-month stress score was included as well. DISCUSSION: This study suggests that perineal lacerations, inflammation, stress, and depressed mood are associated, however, more research is needed to elucidate the actual relationship between inflammation and mental health in women who experience such injuries.